ปัญหากฎหมายเกี่ยวกับธุรกิจขายตรง - วิมิศร นองสุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The Direct Sale is one kind of the distribution channel in business activity. In legally, the Direct Sale is the sale of goods contract but it has particular characteistics which is different from other retailing businesses. The characters of Direct Sale lead to the unfairness to independent distritutor and ultimate consumer. This research finds that the mechanism under the Civil and Commercial Laws of Thailand is not suitable enough to protect and give the justice to the independent distributor and the consumer at large. It was found that the Civil and Commercial Code, the Consumer Protection Act and the Unfair Contract Term Act can not protect such distributor who contracts with the Direct Sale Company from the unfair terms of contract. In case of consumer, the Civil and Commercial Code is not provided a Cooling-off period to the consumer in order to terminate the contract without any dispute. Furthermore the Consumer Protection Act and the Unfair Contract Term Act are not suitable to protect the consumer from misleading advertising on direct sale and the unfair term in contract. Thus, the recommendations to solve such problems are 1. The Direct Selling Company must be notified to the state authority before doing business 2. Some crucial contract terms which are used in direct sale contract between independent distributor and the company must be regulated 3. Providing the Cooling-off period for consumer 4. Providing the Buy Back Policy for independent distributor 5. Proposing the necessary activities of the company 6. Regulating the measures for obstruction the pyramid schemes. The implementation of legal methods should be in the coporation between the Government and Private Sector such as Thai Direct Selling Association. At present, fortunately, the draft of the Direct Selling and Direct Marketing Act, B.C... is on the process which is expected to be passed by the parliament in the near future.